Acute bacterial meningitis among children under five years of age in Oman: a retrospective study during 2000-2005 - Nihar Dash,1,2 Debadatta Panigrahi,2 Saleh Al Khusaiby,3 Salah Al Awaidy,4 Shyam Bawikar.4 (The Journal of Infection in Developing Countries, 2008)
Background: During the last two decades, significant changes have taken place in the epidemiology of meningitis, especially due to the global availability and expanding use of Hib vaccines. The introduction of conjugate Hib vaccine in the Expanded Programme of Immunization (EPI) in Oman and recent availability of meningococcal vaccines against serogroups A and C plus the introduction of pneumococcal heptavalent conjugate vaccine are expected to influence the epidemiology of the disease in the country. We conducted this periodic review of acute bacterial meningitis in children younger than five years of age in Oman from January 2000 to December 2005 to reflect changes in the epidemiological pattern of these pathogens.Methodology: Retrospective analysis of all cases of acute bacterial meningitis in children younger than five years of age reported to the Department of Communicable Diseases Surveillance and Control, Ministry of Health, Oman.Results: There were 344 cases of meningitis due to suspected bacterial etiologies reported in children younger than 5 years of age. Although Haemophilus influenzae 76 (22%) was the most common pathogen identified during the study period, the incidence of meningitis due to Haemophilus influenzae has been dramatically reduced since the introduction of conjugate Hib vaccination in Oman in October 2001. Streptococcus pneumoniae 53 (15%) and Neisseria meningitidis 37 (11%) were the next two leading agents of meningitis respectively. In one hundred seventy four (52%) cases of presumptive bacterial meningitis, the etiologic organism remains unidentified. The peak occurrence of meningitis was in young children younger than one year old. The total male to female ratio was 1.4:1 and the case fatality rate (7deaths) was 2%.Conclusions: With the introduction of Hib vaccine in Oman in October 2001, the absolute number of cases due to Haemophilus influenzae significantly declined over the years. The incidence of meningitis due to other pathogens such as S. pneumoniae and N. meningitidis remains steady. There is significant need to improve laboratory methods of bacterial detection and identification, which will help to formulate better antibiotic policies and strengthen control measures through newly introduced vaccines in Oman.